2010
DOI: 10.1002/eqe.1002
|View full text |Cite
|
Sign up to set email alerts
|

Predicting torsion‐induced lateral displacements for pushover analysis: Influence of torsional system characteristics

Abstract: The increasing popularity of simplified nonlinear methods in seismic design has recently led to many proposals for procedures aimed at extending pushover analysis to plan asymmetric structures. In terms of practical applications, one particularly promising approach is based on combining pushover analysis of a 3D structural model with the results of linear (modal) dynamic analysis. The effectiveness of such procedure, however, is contingent on one fundamental requirement: the elastic prediction of the envelope … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…In general, higher mode effects decrease both in elevation and in plan, with increasing ground motion intensity. Some exceptions, representing extremely torsionally stiff structures, are discussed in De Stefano and Pintucchi (2010); Erduran and Ryan (2010). So, it is difficult to develop a relatively simple approach which would be able to simulate the structural response over the whole range of ground motion intensities that a structure may experience.…”
Section: Background Of the Extended Nmethods And Its Basic Assumptionsmentioning
confidence: 98%
“…In general, higher mode effects decrease both in elevation and in plan, with increasing ground motion intensity. Some exceptions, representing extremely torsionally stiff structures, are discussed in De Stefano and Pintucchi (2010); Erduran and Ryan (2010). So, it is difficult to develop a relatively simple approach which would be able to simulate the structural response over the whole range of ground motion intensities that a structure may experience.…”
Section: Background Of the Extended Nmethods And Its Basic Assumptionsmentioning
confidence: 98%
“…as defined by De Stefano and Pintucchi (2010), i.e. the polar moment of inertia of system strength computed with respect to the axes parallel to the z direction and passing through C R ; -Strength radius of gyration d r ¼ 1 ρL ffiffiffiffiffi I p, f F q non-dimensionalized with respect to the mass radius of gyration ρ.…”
Section: Brief Review Of the Assessment Methods Of Induced Torsional mentioning
confidence: 99%
“…Nevertheless, the basic assumption of the conservativeness of the elastic envelope of lateral displacements with respect to the inelastic one surely needs to be further investigated. De Stefano and Pintucchi (2010) performed a wide parametric analysis on one-storey models and found that the method lose its conservativeness for very torsionally stiff structures, such as shear-walled buildings, for which the inelastic response almost always exceeds the elastic one. This is mainly due to the development of a strength eccentricity related to the failure of one or more components of the structural system, leading to a significant increase of the inelastic torsional effects.…”
Section: Extended N2 Methodsmentioning
confidence: 99%
“…This kind of buildings constitutes the common case in real life so it is urgent to implement updating formulations in these procedures turning the structural response as realistic as possible. Some efforts have been made to take this generation of NSPs to a higher performance level (Chopra and Goel 2004;Fajfar et al 2005;Bento et al 2010;Stefano and Pintucchi 2010;Erduran and Ryan 2010). The Eurocode8-1 (4.3.3.4.2.7 Procedure for the estimation of the torsional effects) includes some guidelines for the determination of torsional effects based on elastic analysis (e.g.…”
Section: Introductionmentioning
confidence: 99%